Membangun Fondasi Keuangan yang Kuat: Hasil Sosialisasi Literasi Keuangan pada Pelajar dan Mahasiswa di Kota Banjarmasin - Rohima, Annisa; Hafizah, Almira Nur; Khodijah, Karlina; Liyanti, Saputri Diva; Jahrah, Siti; Faidah, Anna Nur; Sudirwo, Sudirwo (Damhil: Jurnal Pengabdian kepada Masyarakat, 2024)
Building a Strong Financial Foundation: Results of Financial Literacy Socialization for Students in Banjarmasin. Financial literacy is an important foundation for supporting economic stability in Indonesia. This community service aims to improve financial literacy among students in Banjarmasin City. The methods used include initial observation, socialization through presentation and demonstration, and evaluation of results using pre-test and post-test to measure the level of financial literacy of participants. The evaluation results showed an average effectiveness of 12% increase in participants' understanding of financial literacy which includes financial management, Investment, Capital Markets: Stocks, Bonds, Mutual Funds, Dangers of Illegal Online Loans and Online Gambling. This activity is expected to motivate educated people to share with their peers, friends, and family about financial literacy, and hopefully, the general public can achieve better financial decision-making skills, particularly in Banjarmasin.